Virtual Reality in Radiology: A Systematic Mapping Study - Trevia, Renan; Pinho, Marcio Sarroglia (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
In radiology, virtual reality has emerged as a candidate to solve some issues of the area, such as the ambient lighting and ergonomic postures when diagnosing. The goal of this study is to explore the literature of virtual reality in radiology in order to define and describe the state-of-the-art in addition to finding gaps and opportunities for future research. To do so, we carried out a systematic mapping study covering the period from January 2014 to July 2021. We initially found 329 papers to be reviewed, but after applying our exclusion criteria we ended up with 24 primary studies. Our results suggest that the use of virtual reality has grown recently in the field, however there are many gaps and opportunities to explore in the area.